Augustus Caesar - Walworth, Nancy Zinsser (New York : Chelsea House, 1988)
A biography of the first Roman emperor, under whom Rome achieved great glory.
Includes bibliographical references (p. 108) and index.
Booklist.
School Library Journal.
Wilson's Junior High School.
7.9
7.9
Keywords: Augustus, -- Emperor of Rome, -- 63 B.C.-14 A.D. -- Juvenile literature; Augustus, -- Emperor of Rome, -- 63 B.C.-14 A.D.; Augustus, -- Emperor of Rome, -- 63 B.C.-14 A.D.; Roman emperors -- Biography -- Juvenile literature; Kings, queens, rulers, etc; Kings and rulers -- Biography; Rome -- History -- Augustus, 30 B.C.-14 A.D. -- Juvenile literature; Rome -- History -- Civil War, 43-31 B.C. -- Juvenile literature; Rome -- History -- Augustus, 30 B.C.-14 A.D.; Rome -- History -- Civil War, 43-31 B.C.; Rome -- History